Satisfaction of Senior High School Graduates on Senior High School Tracks: Opportunities and Challenges - Tondo, Josephine; Detecio, Myla (Asia Pacific Higher Education Research Journal (APHERJ), 2021)
Students' satisfaction refers to the short-term perception of learners on certain indicators. The objective of this study is to determine the satisfaction level of 277 purposively selected senior high school (SHS) graduates in the Philippines using six indicators. Findings from the online survey, the following means: assessment (M=3.31); revealed alignment to the track (M=3.22); pedagogy (M=3.20); content (M=3.14); school facilities (M=3.10) and instructional materials (M=2.98). These result shows that the respondents were satisfied in assessment, and least satisfied in instructional materials available. Life and Career Skills such as real-life experiences, confidence/leadership skills, initiative and interaction with others manifested as best practices, while inefficiency of teaching personnel, inadequate track information, insufficient number of teaching personnel and crowdedness exhibited as challenges experienced. This study recommends including qualification and characteristics of teachers, availability of technology, alignment and feedbacks of SHS graduates from the working force and enrolling in technical –vocational course.